Effects of layer number and finger direction on bending behavior of glulam beams - Karagöz İşleyen, Ümmü; Peker, İrfan (BioResources, 2020)
Effects of the number of layers and the number and typology of finger joints were studied relative to the bending behavior of glulam beam made of Scots pine (Pinus sylvestris) laminates. The investigated parameters of glulam beams with constant overall dimensions (width × depth × length) of 90 mm × 90 mm × 1710 mm were lamination thickness (18 mm or 30 mm), the distance of the finger joints (200, 400, and 600 mm), and finger direction (horizontal and vertical). A total of 14 experimental samples were produced (12 different finger joint beams and two reference beams without finger joints) and tested under four-point bending tests. Taguchi orthogonal experimental design was used to evaluate and optimize test results using the S/N ratio. The effects of main and interactions between producing parameters on strength of glulam beam were determined by variance analysis. According to the results of the analysis, it was determined that the number of layers and the direction of the finger had a significant effect on the flexural strength of the beams, but the finger distance was not significant. Moreover, the highest strength values were obtained in 5-layer finger-jointed beams with vertical finger direction.